2021
DOI: 10.1172/jci.insight.150405
|View full text |Cite
|
Sign up to set email alerts
|

Cardiomyocyte microRNA-150 confers cardiac protection and directly represses proapoptotic small proline–rich protein 1A

Abstract: MicroRNA-150 (miR-150) is downregulated in patients with multiple cardiovascular diseases and in diverse mouse models of heart failure (HF). miR-150 is significantly associated with HF severity and outcome in humans. We previously reported that miR-150 is activated by β-blocker carvedilol (Carv) and plays a protective role in the heart using a systemic miR-150 KO mouse model. However, mechanisms that regulate cell-specific miR-150 expression and function in HF are unknown. Here, we demonstrate that potentially… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(34 citation statements)
references
References 44 publications
9
25
0
Order By: Relevance
“…Since miR-150 negatively regulates CM apoptosis in vitro and in vivo [ 25 , 26 ], we next examined whether the novel upstream regulator of miR-150, Gm41664 regulates CM apoptosis. We first find that Gm41664 knockdown in CMs decreases apoptotic p53 , Casp14 , and Ing-4 while miR-150 knockdown increases the expression of these apoptotic genes (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Since miR-150 negatively regulates CM apoptosis in vitro and in vivo [ 25 , 26 ], we next examined whether the novel upstream regulator of miR-150, Gm41664 regulates CM apoptosis. We first find that Gm41664 knockdown in CMs decreases apoptotic p53 , Casp14 , and Ing-4 while miR-150 knockdown increases the expression of these apoptotic genes (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We showed using a miR-150 KO mouse model that miR-150 is protective in MI by decreasing CM apoptosis [ 25 ]. We also demonstrated that CM-specific miR-150 cKO mice worsen apoptosis and adverse remodeling post-MI [ 26 ]. Another group reported that miR-150 overexpression protects the heart from acute MI by suppressing the monocyte migration [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Low circulating levels of miR-150 were associated with LV remodeling after first ST-elevation acute MI ( 46 ). During acute MI, expression of miR-150 was remarkably decreased; restoration of its expression could improve cardiac function, reduce infarct areas, and attenuate fibrosis ( 47 50 ). Mechanically, miR-150 could reduce monocyte accumulation to myocardium by inhibiting CXCR4, decrease CMs apoptosis through repressing pro-apoptotic genes small proline–rich protein 1a (SPRR1a), egr2 and p2×7r, and prevent activation of CFs via downregulating pro-fibrotic Homeobox a4 (Hoxa4) ( 47 50 ).…”
Section: Non-coding Rnas In Cardiac Fibrosismentioning
confidence: 99%
“…MicroRNAs (miRNAs, miRs) from plasma exosomes have been reported to be ideal biomarkers for the early identification of cardiovascular disease and to have great potential for therapeutic and other applications (11,12). There is evidence to suggest that a series of important physiological processes, including the survival, proliferation and angiogenesis of cardiomyocytes are regulated by miRNAs (13,14). In addition, miRNAs have been shown to stimulate cardiomyocyte proliferation and promote cardiac repair (15,16).…”
Section: Introductionmentioning
confidence: 99%